Chemical composition and fatty acid profile of BRS Capiaçu ensiled at different regrowth ages - Lopes, Fernando César Ferraz; Morenz, Mirton José Frota; Lédo, Francisco José da Silva; Carneiro, Jailton da Costa; Paciullo, Domingos Sávio Campos; Andrade, Paulino José Melo; Moraes, Conrado Trigo de (Semina: Ciências Agrárias, 2021)
This study aimed to evaluate the chemical composition and fatty acid (FA) profile of chopped forage and silage of BRS Capiaçu elephant grass at four regrowth ages: 50, 70, 90 and 110 days. A randomized block design with five replications was used. The ensiling was carried out manually in experimental silos without wilting using no additives or bacterial inoculants. The results were analyzed using mixed models (P smaller 0.05). The model included treatment (regrowth age) as a fixed effect and block as a random effect. Linear and quadratic effects of the treatments were analyzed using orthogonal contrasts. There were linear increases in the dry matter (DM, g kg -1) and lignin (g kg -1 DM) contents and linear reductions in the in vitro DM digestibility (g kg -1) of chopped grass and silage as a function of regrowth age (P smaller 0.001). Quadratic effects (P smaler 0.01) were observed for the chopped grass contents (g kg-1 DM) of crude protein (CP), ether extract (EE) and neutral detergent fiber (NDF) as a function of regrowth age. There were linear decreases (P smaler 0.0001) in the CP content (g kg-1 DM) and pH and linear increases (P smaler 0.001) in the EE and NDF contents (g kg-1 DM) in the silage as a function of regrowth age. There were linear decreases (P smaler 0.01) in the chopped grass contents and linear increases (P smaler 0.05) in the silage contents of total FAs, linoleic and alfa-linolenic acids (g kg-1 DM) as a function of regrowth age. BRS Capiaçu elephant grass must be harvested at up to 70 days of regrowth to obtain forage with good nutritional value and the highest levels of linoleic and alfa-linolenic acids (g kg-1 DM). To produce silages with adequate pH values and the highest levels of linoleic and alfa-linolenic acids (g kg-1 DM), BRS Capiaçu must be harvested between 90 and 110 days of regrowth.